Psychological distress in the face of a pandemic: An observational study characterizing the impact of COVID-19 on immigrant outpatient mental health. (January 2021) - Serafini, Randal A.; Powell, Samuel K.; Frere, Justin J.; Saali, Alexandra; Krystal, Hannah L.; Kumar, Vedika; Yashaswini, Chittampalli; Hernandez, Josimar; Moody, Kate; Aronson, Anne; Meah, Yasmin; Katz, Craig L.
Highlights: Undocumented immigrant outpatients showed increased depression and anxiety during COVID-19. The pandemic was directly associated with increased psychological distress levels. Telephone-based telepsychiatry helped patients manage their mental health during the pandemic. Depressive disorders and comfort during telepsychiatry strongly influenced distress levels. Abstract: Undocumented immigrants have disproportionately suffered during the novel coronavirus disease 2019 (COVID-19) pandemic due to factors including limited medical access and financial insecurity, which can exacerbate pandemic-associated distress. Psychological outcomes for immigrant outpatients were assessed after transition to telepsychiatry in March 2020. Mental health was assessed with Patient Health Questionnaire (PHQ-2) and Generalized Anxiety Disorder (GAD-2) inventories, a novel coronavirus-specific survey, and the Kessler Psychological Distress Scale (K10+). Feedback on telepsychiatry sessions and access to non-clinical resources were also gathered, after which multivariable linear regression modeling identified psychosocial factors underlying changes in distress levels. 48.57% and 45.71% of participants reported worsened anxiety and depression levels due to the pandemic, respectively. From March to April, PHQ-2 and GAD-2 scores significantly increased by 0.81 and 0.63 points, respectively. The average total psychological distress score was 23.8, with 60% of scores reflecting serious mental illness. Factors that most influenced K10+ scores included a pre-existing depressive disorder, food insecurity, and comfort during telepsychiatry visits. 93.75% of participants believed access to remote psychiatry helped their mental health during COVID-19. The negative impact of COVID-19 on mental health in vulnerable populations stems from medical and psychosocial factors such as pre-existing psychiatric conditions and unmet essential needs.